2014
DOI: 10.1002/cne.23572
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of layer‐specific cadherin expression profiles and maintenance of cytoarchitectonic areas in the allocortex of the reeler mutant mouse

Abstract: Cadherins are calcium-depending cell adhesion proteins that play critical roles in brain morphogenesis and wiring. They provide an adhesive code for the development of cortical layers, due to their homophilic interactions and their restricted spatiotemporal expression patterns. In the adult organism, cadherins are involved in the maintenance and plasticity of neuronal circuits that play a role in learning. A well-known model for studying corticogenesis is the reeler mouse model. Numerous investigations of neoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
(83 reference statements)
3
8
0
Order By: Relevance
“…In the present work, we study the expression profiles of Pcdh19 and Ncdh in the limbic structures in postnatal brain sections. Our data corroborate previous studies on the expression of Pcdh19 (Gaitan & Bouchard, ; Kim, Chung, Sun, & Kim, ; Dibbens et al, ; Hertel et al, ; Stoya, Redies, & Schmid‐Hertel, ) and Ncdh (Redies & Takeichi, ; Obst‐Pernberg et al, ). We extend these studies by adding more detail and provide an extensive overview of expression of both cadherins in the limbic structures, such as the amygdala, the hippocampus and the ventral hypothalamus.…”
Section: Discussionsupporting
confidence: 92%
“…In the present work, we study the expression profiles of Pcdh19 and Ncdh in the limbic structures in postnatal brain sections. Our data corroborate previous studies on the expression of Pcdh19 (Gaitan & Bouchard, ; Kim, Chung, Sun, & Kim, ; Dibbens et al, ; Hertel et al, ; Stoya, Redies, & Schmid‐Hertel, ) and Ncdh (Redies & Takeichi, ; Obst‐Pernberg et al, ). We extend these studies by adding more detail and provide an extensive overview of expression of both cadherins in the limbic structures, such as the amygdala, the hippocampus and the ventral hypothalamus.…”
Section: Discussionsupporting
confidence: 92%
“…7 ). Recent work using double ISH labeling validates the layer-specific expression patterns we find for cadherins in the MEC [ 23 ], while other well-characterized genes such as reelin and calbindin [ 22 , 75 ] also have expected expression patterns. Our analysis identifies a further 767 genes with layer-specific or enriched expression and 799 genes with dorsoventral expression.…”
Section: Discussionsupporting
confidence: 62%
“…Our understanding of the architecture and functions of MEC may benefit from similar approaches. While detailed anatomical and histochemical studies have shown that certain genes, including reelin, calbindin [ 22 ] and some cadherins [ 23 ], identify cell populations associated with particular layers of the MEC, we know very little about the identity, laminar or dorsoventral organization of the vast majority of genes expressed in the MEC. This is a difficult problem to address for the MEC as its borders with adjacent structures are ambiguous, it has a dorsoventral as well as a laminar organization and its similarity to other cortical structures is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports on expression of these cadherins in embryonic vertebrate CNS (Wohrn et al, 1998, 1999; Redies et al, 2001; Becker and Redies, 2003; Luo et al, 2004; Gaitan and Bouchard, 2006; Liu et al, 2006; Emond et al, 2009; Tai et al, 2010; Liu et al, 2010; Terakawa et al, 2013), but only a few on their distribution in the brain of adult vertebrates (Dean et al, 2007; Kim et al, 2007; Hertel et al, 2008, 2012; Hertel and Redies, 2011; Stoya et al, 2014). Moreover, studies on their expression in the adult brains focus mainly on a subset of brain structures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In developing and adult mice and rats, pcdh17 and pcdh19 are detected in most cortical regions, basal ganglia, amygdale and/or hippocampus (Kim et al, 2007; Hertel et al, 2008; Hertel and Redies, 2011; Stoya et al, 2014). Both pcdhs are found in zebrafish dorsal telencephalon (pallium).…”
Section: Discussionmentioning
confidence: 99%